Psychological hardness and its relationship to Marital compatibility among a sample of primary school teachers in the wilaya of Djelfa - DJENIDI, Fatima zohra; BAHI, Selami (Social Sciences Journal, 2024)
The current study aims to identify the nature of the relationship between psychological hardness and marital compatibility among a sample of primary school teachers in the wilaya of Djelfa, and to reveal their level the study’s sample. The study was conducted on a sample of (60) female teachers. The descriptive approach was used, as well as the psychological hardness scale of Imad Mukhaimer (2002), which was codified by Bashir Maamaria (2019) on the Algerian environment, in addition to the marital compatibility scale of Iman Mahmoud Obeid (2014).The data were processed statistically based on the SPSS25 program, relying on the appropriate statistical methods. Thestudy resulted in the existence of a positive and statistically significant correlation between psychological hardness and marital compatibility among the study sample. It also found that the level of psychological hardness is high, and the level of marital compatibility is average for a sample of primary school teachers in the wilaya of Djelfa. Keywords: Psychological hardness, Marital compatibility, Primary school teachers.